PENERAPAN SISTEM INTEGRATED RAHARJA MULTIMEDIA E-PORTFOLIO (iRME) CV ONLINE PADA PERGURUAN TINGGI RAHARJA - Untung Rahardja; Muhamad Yusup; Erni Astuti (CCIT Journal, 2014)
Developments in technology , especially Internet technology has supported to provide various types of services that can be accessed easily , quickly , efficiently , whenever and wherever , as well as allowing the use of e – portfolios . E – Portfolio is based on the application of advanced users to store , organize , and share items that represent the individual learner . Therefore , making an application e – portfolio system is highly recommended right . With methods based system online , the e – portfolio system will be very easy to use . E – portfolio is called iRME in Perguruan Tinggi Raharja. In this article described the problems that arise and solving the problem examined . In addition there are 5 ( five ) advantages of this application . In the implementation of the prototype view of iRME application . It can be concluded that the contribution iRME system can accommodate and facilitate private lifetime collection efforts Pribadi Raharja in personal portfolios . By implementing iRME on Perguruan Tinggi Raharja expected Pribadi Raharja to ease in making the Curriculum Vitae ( CV ) of quality .